Cost-Effectiveness Analysis on Endoscopic Surveillance Among Western Patients With Barrett's Esophagus for Esophageal Adenocarcinoma Screening. Issue 39 (September 2015) - Yang, Yu; Chen, Hai-Ning; Wang, Rui; Tang, Yun-Jing; Chen, Xin-Zu
Abstract : Abstract: Incidence of esophageal adenocarcinoma (EAC) has risen rapidly over the past decades in Western countries. As a premalignant lesion, Barrett's esophagus (BE) is an established risk factor of EAC. This study estimated the impact of surveillance endoscopy for BE on population's survival upon EAC by a whole-population cost-effectiveness analysis among modeled Western population. Possibilities and survival payoffs were retrieved through literature searching based on PubMed database. Patients with BE were classified as adequate surveillance (AS), inadequate surveillance (IAS), and no surveillance groups. Direct cost of endoscopy per person-year was estimated from diagnosis of BE to before diagnosis of EAC in the whole-population model, whereas the payoff was 2-year disease-specific survival rate of EAC. AS for patients with BE had lower cost-effectiveness ratio (CER) than that of IAS group, as well as lower incremental cost-effectiveness ratio (6116 [Euro sign]/% vs 118, 347 [Euro sign]/%). Prolonging the surveillance years could decrease the yearly cost in whole population and also relevant CERs, despite increased total cost. Increasing the proportion of participants in AS group could improve the survival benefit. The maximal payoff was up to 2-year mortality reduction of 2.7 per 100, 000 persons by spending extra [Euro sign]1, 658, 913 per 100, 000 person-years. A longer endoscopic surveillance among BE subpopulation plan can reduce yearly budget. Attempt to increase the proportion of AS participants can induce decline in population mortality of EAC, despite extra but acceptable expenditure. However, regarding optimal cost-effectiveness, further studies are still required to identify a high-risk subpopulation out of BE patients for endoscopic surveillance.